Global industry perspective of halal cosmetics applying sales and distribution process based on enterprise resources planning - Mefid, Khairen Niza; Ridwan, Ari Yanuar; Sari, Warih Puspita (Bulletin of Social Informatics Theory and Application, 2019)
The cosmetics industry has several business processes from procurement to sales and distribution of products; thus, it requires a system that can integrate and monitor business processes under halal standardization. This paper discusses the use of ERP systems in the application of Odoo 10.0 Halal sales and distribution modules using the ASAP (Accelerated SAP) method. Halal system integration allows users to find out the sales results in real-time and can do documentation in the form of customer data, quotations, sales orders, invoices, delivery orders. In addition, the main element is the halal report on sales management that can store and show reports for the marketing department. This halal ERP system can be adapted to the needs of companies to face global challenges.